2008
DOI: 10.1111/j.1747-0765.2007.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel root-determined hypernodulation mutantrdh1ofLotus japonicus

Abstract: A mutant line that develops an excess number of small nodules was found in Lotus japonicus Miyakojima MG20 during a screening for mutants defective in nodule development and nitrogen fixation. Genetic analysis revealed that the phenotype is inherited in a monogenic, recessive manner. The gene's locus was mapped on chromosome 1 between 53.7 and 61.4 cM. This mutant formed 5-10-fold more nodules than the wild-type plant, and a grafting experiment revealed that the root regulated the hypernodulation. Except for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…However, the RDH1 gene is unlikely to be the same as the ENF1 gene, because the phenotype of rdh1 is inherited in a monogenic, recessive manner, whereas enf1 is monogenic but incompletely dominant. Moreover, except for the nodulation phenotype, no other differences were observed in growth traits between rdh1 and wild-type plants (Ishikawa et al, 2008).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the RDH1 gene is unlikely to be the same as the ENF1 gene, because the phenotype of rdh1 is inherited in a monogenic, recessive manner, whereas enf1 is monogenic but incompletely dominant. Moreover, except for the nodulation phenotype, no other differences were observed in growth traits between rdh1 and wild-type plants (Ishikawa et al, 2008).…”
Section: Discussionmentioning
confidence: 80%
“…In C, the significance of differences among four groups was determined by the two-tailed multiple t test with Bonferroni correction following ANOVA (six comparisons in four groups), and the different letters refer to significant differences at P , 0.01. fixation activity is elevated without deleterious effects on plant growth and development have been limited. One exception is the L. japonicus root-determined hypernodulation1 (rdh1) mutant, which also exhibits a hypernodulation and enhanced nitrogen fixation phenotype (Ishikawa et al, 2008). However, the RDH1 gene is unlikely to be the same as the ENF1 gene, because the phenotype of rdh1 is inherited in a monogenic, recessive manner, whereas enf1 is monogenic but incompletely dominant.…”
Section: Discussionmentioning
confidence: 99%
“…Splitroot and grafting experiments have demonstrated that in many legumes, control of nodule number involves long-distance signaling from the shoot to the root (Bauer, 1981;Kosslak and Bohlool, 1984;CaetanoAnollés and Gresshoff, 1991;Sagan and Duc, 1996;Krusell et al, 2002;Nishimura et al, 2002a;Penmetsa et al, 2003;Oka-Kira and Kawaguchi, 2006). Other evidence shows that local tissues also have a role in signaling: (1) in some mutants, the root genotype controls nodule number; and (2) application of hormones directly to the roots can change nodule number (Jacobsen and Feenstra, 1984;Hirsch and Fang, 1994;Prayitno et al, 2006;Ishikawa et al, 2008). Analysis of local and long-range auxin transport in nodulating legumes showed that inoculation is accompanied by a local change in auxin transport that is thought to be necessary for nodule initiation (Mathesius et al, 1998;Boot et al, 1999;Pacios Bras et al, 2003;Huo et al, 2006;Subramanian et al, 2006Subramanian et al, , 2007Zhang et al, 2007a) and by a decrease in long-range auxin flux from the shoot to the root.…”
mentioning
confidence: 99%
“…The supernodulation phenotype of sickle mutants, which have disrupted ethylene signaling, demonstrates the role of ethylene in controlling nodulation. The mutants rdh1, tml, and plenty of L. japonicus and nod3 of pea-like har1/sym29/nark/ sunn, form short roots with excessive nodules and nodulate in the presence of nitrate, but the nodulation phenotype of a grafted plant depends on the genotype of the root, not the shoot (Postma et al, 1988;Ishikawa et al, 2008;Magori et al, 2009;Yoshida et al, 2010). None of these mutants appear to have a defect in ethylene signaling.…”
mentioning
confidence: 99%